The Study of Phosphate Release from Artificial Sediment into Water Body Using Diffusive Gradient in Thin Film (DGT) Device in Oxic Condition - Ardina Purnama Tirta; Asep Saefumillah; Foliatini Foliatini; Herawati Herawati (Indonesian Journal of Chemistry, 2020)
The phenomenon of phosphate release in sediments into water bodies under oxic environment has been investigated using the Diffusive Gradient in Thin Film (DGT) technique. This research consists of several stages: polymer synthesis and DGT probe assembly, sediment sampling, DGT deployment in oxic conditions, and phosphate analysis from DGT adsorption results. Acrylamide polymer was successfully synthesized with a composition 15% acrylamide; N-N'-methylenebisacrylamide 0.1% and ferrihydrite as binding gels. DGT probes were assembly by placing a 16 x 3.2 cm polyacrylamide gel, binding gels and filter membranes on the DGT probes. The sediment sample was taken from the Bogor Botanical Gardens at the coordinates 6°36’00.6” S; 106°47’51.0” E. The DGT probe was placed in sediment samples for 1, 3 and 7 days in oxic conditions. After the prescribed time, the binding gel was removed and cut every 1 cm depth, then eluted using 0.25 M H2SO4 and the phosphate concentration was measured using spectrophotometry method. The results showed that the phosphate concentration tends to be higher with the increasing incubation time and depth. Maximum CDGT phosphate released on day 1, day 3 and day 7 were 1.00 µg/L at a depth of 14 cm, 6.61 µg/L at a depth of 14 cm, and 20.92 µg/L at a depth of 11 cm respectively. This ensures that the phosphate in water bodies comes from biogeochemical processes that occur in sediments and is successfully measured through DGT techniques.